Pengaruh Kejutan Suhu Panas dan Lama Waktu Setelah Pembuahan Terhadap Daya Tetas dan Abnormalitas Larva Ikan Nila (Oreochromis niloticus) [The Thermal Temperature Shock and Time After Fertilization In Hatching Rate and Abnormality Of Nile Fish (Oreochromis niloticus) ] - Akhmad Taufiq Mukti; Herliana Arsianingtyas; Sri Subekti (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
AbstractThe chromosome manipulation in fish is one of the strategy that will be used to produce of the high generation and good quality in its genetics, as follow fast to grow, disease resistant, high survival, tolerate with environment exchange and easy to be cultured. One of manipulation chromosome the method in fish used thermal temperature shock. The aim of the study was to know the thermal temperature shock and the time after fertilization forward hatching rate and abnormality of nile fish larvae and also to know the thermal temperature shock and the time after fertilization that resulted the best hatching rate and abnormality in nile fish larvae. The method was Factorial Completed Randomized Design as experimental design. The treatment used temperatures shock were 40ºC, 41ºC and 42ºC as long as 2,5 minutes, with the time of 80, 85 and 90 minutes after fertilization, each treatment was four replications. The primary parameter was hatching rate and abnormality of nile fish larvae and the secondary parameter were fertilization and water quality. The result showed that the thermal temperature shock was significantly influenced to hatch rate and abnormality, but the time of shocking after fertilization and the interaction between them showed were not significantly influenced to hatch rate and abnormality. The highest of hatching rate and abnormality percentage was showed by the treatment with shocking 40°C was 90,77 percent and 2,60 percent.